PENGARUH RELIGIOUS BELIEF DAN HALAL CERTIFICATION TERHADAP PURCHASE INTENTION MELALUI HALAL AWARENESS SEBAGAI VARIABEL INTERVENING PADA PRODUK KOSMETIK HALAL WARDAH - Agustiyaningrum, Erna Widya; Maharani, Bernadetta Diansepti; Kusumaningrum, Nonik (JURNAL MANAJEMEN MOTIVASI, 2025)
This study investigates the influence of religious belief and halal certification on purchase intention, with halal awareness as a mediating variable in Wardah halal cosmetics. A quantitative method was applied to 160 respondents using questionnaires. Data were analyzed through multiple regression and the Sobel test. Results reveal that religious belief and halal certification positively affect halal awareness. Furthermore, halal awareness and halal certification significantly influence purchase intention, while religious belief only has an indirect effect. These findings highlight the role of halal awareness in bridging religiosity and consumer behavior in halal cosmetic marketing.